Ceramsite-gypsum solid waste system rock-like similar material as well as preparation method and application thereof

By regulating the mass ratio of the ceramic-gypsum solid waste system materials and the addition of retarder, the problems of high uniaxial compression strength and high cost of rock-like materials in the prior art were solved, and ceramic particles that meet the requirements of low strength and high brittle performance were prepared. -Gypsum solid waste system material, suitable for simulation of coal mining projects.

CN119306461AActive Publication Date: 2025-01-14ANHUI UNIV OF SCI & TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411424753.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

When simulating the requirements of low strength and high brittle performance, existing rock-like materials have problems such as high uniaxial compression strength, high raw material cost and long preparation cycle, which cannot meet the scientific simulation needs of coal mining projects.

Method used

The mechanical properties of the material are regulated by controlling the mass ratio of desulfurization gypsum and water-absorbing ceratops and mass ratios of water to desulfurization gypsum, and the curing time of desulfurization gypsum is adjusted through retarder. Low-strength and high-brittle materials with simulated strength not exceeding 3MPa and brittle index of 0.15 to 0.23 are produced.

Benefits of technology

The preparation of low-strength and high-brittle materials is achieved, which meets the simulation needs of coal mining projects, reduces raw material costs and preparation cycles, and ensures the mechanical properties and brittle damage characteristics of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306461A_ABST
    Figure CN119306461A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rock-like materials, and discloses a ceramsite-gypsum solid waste system rock-like similar material as well as a preparation method and application thereof, and the ceramsite-gypsum solid waste system rock-like similar material is prepared from desulfurized gypsum, water-absorbing ceramsite, a retarder and water; the mass ratio of the desulfurized gypsum to the water-absorbing ceramsite to the retarder is (200-400): (5-50): (0.5-0.9); the mass ratio of the water to the desulfurized gypsum is (0.43-0.47): 1; the water-absorbing ceramsite is obtained by soaking ceramsite with water. By limiting the mass ratio of the water to the desulfurized gypsum and the mass ratio of the desulfurized gypsum to the water-absorbing ceramsite, the low-strength and high-brittleness material with the simulation strength not exceeding 3 MPa and the brittleness index of 0.15-0.23 is obtained, the brittle failure characteristic is shown, the requirement for the low-strength and high-brittleness similar material is met, and the low-strength and high-brittleness material can be widely applied to the field of building materials. The problems that a hard rock similar model test material prepared in the prior art is high in strength and low in brittleness index are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of rock-like materials, and in particular relates to a ceramsite-gypsum solid waste system rock-like material and a preparation method and application thereof. Background Art

[0002] In the relevant research on coal mining, it is often necessary to carry out dynamic simulation tests on the rock failure process. In the test, similar materials need to be made into similar models, and then the deformation and failure of similar models under external influences are observed. The deformation and failure of rocks can be deduced according to the similarity criterion, providing a scientific basis for the design of coal mining projects.

[0003] Most of the rock-like materials disclosed so far use quartz sand and cement as aggregate and binder, which have long maintenance cycles and high raw material costs. Due to the high bonding strength of the hydration products, the uniaxial compression strength of the prepared rock-like materials is as high as tens of MPa, which shows obvious limitations for simulating rock-like materials with low strength and high brittleness requirements.

[0004] The prior art discloses a similar material for extrusion 3D printing of tunnel lining models. Referring to Chinese patent CN118084433A, the density of the similar material is 21.4 g / cm 3 ~23.2g / cm 3 , compressive strength is 473.4kPa~1804.6kPa, elastic modulus is 371.8MPa~1332.9MPa, and tensile strength is 45.1kPa~128.4kPa. This technology uses traditional quartz sand and cement as aggregate and binder, requires specific conditions for curing, has a long preparation cycle, high production cost, and the strength of the prepared similar materials is high, which cannot meet the requirements of low strength and high brittleness. Chinese patent CN109679291A discloses a transparent hard rock similar model test material and its preparation method, which is prepared by 25 parts of epoxy resin, 25 parts of modified curing agent, and 0~5 parts of saturated alcohol rosin solution, and the compressive strength is between 10 and 100MPa. The raw materials epoxy resin and curing agent used in this technology are chemical reagents, the raw material cost is relatively high, and it cannot achieve the conditions of low strength and high brittleness. Chinese patent CN105967562A discloses a hard rock similar model test material and a preparation method thereof, which uses fine river sand, barite powder, silicone rubber, rosin and alcohol as raw materials, and obtains a similar model test material with hard rock stress-strain characteristics through different mass ratios; the material has a low uniaxial compression strength in the range of 1.2MPa to 1.6MPa, a low brittleness index, and cannot meet the requirements of low strength and high brittleness. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a ceramsite-gypsum solid waste system rock-like material and a preparation method and application thereof.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows.

[0007] A ceramsite-gypsum solid waste system rock-like material, prepared from desulfurized gypsum, water-absorbing ceramsite, retarder and water;

[0008] The mass ratio of the desulfurized gypsum, the water-absorbing ceramsite and the retarder is 200-400: 5-50: 0.5-0.9;

[0009] The mass ratio of the water to the desulfurized gypsum is 0.43-0.47:1; the water-absorbing ceramsite is obtained by soaking the ceramsite in water.

[0010] The present invention controls the mass ratio of desulfurized gypsum and water-absorbing ceramsite, as well as the mass ratio of water to desulfurized gypsum, to adjust the mechanical properties of the rock-like material of the ceramsite-gypsum solid waste system, thereby obtaining low-strength and high-brittle material properties. The curing time of the desulfurized gypsum is then adjusted by the amount of retarder added to prevent the curing time of the desulfurized gypsum from being too long or too short. The rock-like material of the ceramsite-gypsum solid waste system in the present invention can meet the demand for low-strength and high-brittle materials, and its simulated strength does not exceed 3MPa and the brittleness index is 0.15 to 0.23.

[0011] In another preferred embodiment, the retarder is a plant protein retarder. The retarder can ensure the retarding time of the desulfurized gypsum. Gypsum retarders are mainly divided into organic acid salts, phosphates and proteins. Organic acid salts mainly include citric acid, citrate, tartaric acid and tartrates, which have significant retarding effects, but the dosage is large and the strength loss of gypsum materials is large. Phosphates mainly include pyrophosphate, sodium tripolyphosphate, sodium polyphosphate, etc., which have large dosages and poor retarding effects, and significantly reduce the strength of gypsum. Protein retarders have the advantages of small dosage, significant retarding effects and little effect on gypsum strength. Therefore, plant protein coagulants have the advantages of small dosage, good retarding effects, low cost, and environmental protection.

[0012] In another preferred embodiment, the particle size of the ceramsite is 0.8 cm to 1.4 cm, and the particle size of the desulfurized gypsum is 10 μm to 25 μm. This particle size allows the ceramsite to be evenly dispersed in the desulfurized gypsum and the retarder, ensuring the low-strength and high-brittleness characteristics of the mechanical properties of rock-like materials in the ceramsite-gypsum solid waste system. Therefore, it is necessary to select ceramsite with a particle size within a certain range to form a uniform network structure. If the particle size of the ceramsite is too small, the strength of the material will be greatly improved, and if the particle size is too large, it will be unfavorable for molding.

[0013] In another preferred embodiment, the soaking time is 1 h to 2 h.

[0014] The second object of the present invention is to protect the preparation method of the rock-like material of the ceramsite-gypsum solid waste system, which specifically comprises the following steps:

[0015] Mix desulfurized gypsum, retarder and water according to the mass ratio, add water-absorbing ceramsite and continue to stir to obtain a mixed slurry;

[0016] The mixed slurry is injected into a mold and compacted to obtain a sample;

[0017] The sample is cured at 23° C. to 27° C. for 24 h to 48 h, then demolded and dried to constant weight to obtain the ceramsite-gypsum solid waste system rock-like material.

[0018] In another preferred embodiment, the mixing speed is 60r / min to 150r / min, and the time is 3min to 5min. The stirring rate will affect the stirring efficiency and the curing time of desulfurized gypsum. The curing time of desulfurized gypsum in water is within a certain range. If the stirring rate is too fast, a certain amount of heat will be generated during the stirring process, accelerating the curing. If the stirring rate is too slow, the stirring is insufficient, resulting in partial curing.

[0019] In another preferred embodiment, the drying temperature is 30-40°C and the drying time is 12-40 hours. Under this temperature, the material is uniformly dried and solidified at a constant temperature, ensuring that the moisture inside the material is removed slowly and evenly, and preventing the sample from cracking due to excessive temperature or uneven drying.

[0020] In another preferred embodiment, the compaction standard is that there are no bubbles on the surface of the mixed slurry.

[0021] The third object of the present invention is to protect the application of the rock-like materials of the ceramsite-gypsum solid waste system in rock simulation experiments.

[0022] In another preferred embodiment, the ceramsite-gypsum solid waste system rock-like material is used to simulate low-strength and high-brittle rock simulation materials with a uniaxial compression strength not exceeding 3 MPa.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention obtains a low-strength and high-brittle material by controlling the addition amount of desulfurized gypsum and ceramsite, and adjusts the curing time of the desulfurized gypsum by the addition amount of the retarder to prevent the curing time of the desulfurized gypsum from being too long or too short. Controlling the mass ratio of water to desulfurized gypsum can effectively control the curing time and the mechanical properties of the prepared ceramsite-gypsum solid waste system rock-like material. The ceramsite-gypsum solid waste system rock-like material in the present invention can simulate a low-strength and high-brittle material with a strength not exceeding 3MPa and a brittleness index of 0.15 to 0.23, and exhibits brittle failure characteristics, which meets the requirements for low-strength and high-brittle similar materials.

[0025] (2) The present invention controls the mass ratio of water to desulfurized gypsum during the preparation process, mainly because if the water-to-paste ratio is too high, the water is difficult to remove, the curing time is too long, the fluidity of the slurry is too large, and the ceramsite is easy to float on the surface of the slurry due to its porous structure, affecting the dispersion of the ceramsite in the slurry. If the water-to-paste ratio is too low, the curing rate of the slurry is accelerated, the fluidity is low, the slurry is difficult to stir evenly, and the internal bubbles are difficult to discharge, which will also seriously affect the uniformity of similar material structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a stress-strain curve diagram of rock-like materials of the ceramsite-gypsum solid waste system with different ceramsite contents in the present invention; wherein, a is the stress-strain curve diagram of T6; b is the stress-strain curve diagram of T5; c is the stress-strain curve diagram of T4; d is the stress-strain curve diagram of T3; e is the stress-strain curve diagram of T2; and f is the stress-strain curve diagram of T1.

[0027] Figure 2 1 is a stress-strain curve of the cubic specimen in Example 2 of the present invention and a sample diagram after uniaxial compression strength test; a is a stress-strain curve diagram, in which illustration a1 is a sample photo after uniaxial compression strength test; b is an internal cross-sectional diagram.

[0028] Figure 3 This is the SEM image of the cubic sample in Example 2 of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the specific implementation of the present invention to clearly and completely describe the technical solution in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.

[0031] The experimental raw materials used in the following examples are:

[0032] (1) Ceramic aggregate: The performance index D50 is a particle size of 0.8 cm to 1.4 cm, purchased from Jincai Building Materials Sales Co., Ltd. In the present invention, the ceramic aggregate is used as an aggregate in a rock-like material.

[0033] (2) Desulfurization gypsum: 600 mesh, from Henan Wuhu Environmental Protection Technology Co., Ltd., is an industrial by-product produced by limestone desulfurization of flue gas after coal combustion, and serves as a binder.

[0034] (3) Retarders: One of the main drawbacks of desulfurized gypsum in cementitious materials is its short setting time. This is not conducive to the production and application of desulfurized gypsum as a cementitious material. Therefore, retarders are added to the application of desulfurized gypsum to adjust the hydration rate and setting time. Gypsum retarders are mainly divided into organic acids and soluble salts, alkaline phosphates and macromolecular protein compounds. The present invention uses a protein retarder, the mechanism of which is that protein and its hydrate are adsorbed on the surface of dihydrate gypsum particles to prevent germ formation, or form protective colloids to hinder the hydration of hemihydrate gypsum. It is a white powder produced by Beijing Kelly Tianwei Chemical.

[0035] 1. Equipment and instruments used:

[0036] (1) Electronic analytical balance: weighing accuracy is 0.1 mg, maximum range is 200 g, used for weighing raw materials and retarders.

[0037] (2) Planetary cement slurry mixer: used to mix raw materials with water to make them uniform. In the embodiment of the present invention, the gypsum slurry was stirred for 1 minute, and then stirred for another 1 minute after adding ceramsite.

[0038] (3) Standard Favica apparatus: This instrument is manufactured according to ISO9597-1989 and is used to determine the setting time of gypsum slurry.

[0039] (4) Steel ruler: This experiment is used to determine the fluidity of gypsum slurry.

[0040] (5) Electric constant temperature air drying oven: used to dry samples and utensils. In the embodiment of the present invention, the operating temperature is 20°C, the drying time is 24h, and the maximum operating temperature is 25°C.

[0041] (6) Electronic universal testing machine: Model WDW-50, used to perform uniaxial compression tests and mechanical property tests on samples. The testing machine controls loading by controlling the displacement size, and the loading speed is 0.6 mm / min. This ensures that the obtained stress-strain curve is complete and reliable, while avoiding damage to the testing machine caused by sudden destruction of the specimen.

[0042] (7) X-ray diffractometer: Model: XRD-6000, with a scanning range of 10° to 80° (2θ), used to analyze the phase composition of the specimen.

[0043] (8) Scanning electron microscope: Model S-3000N, used for high-resolution microscopic morphology analysis of sample surfaces, with a magnification of 500-30,000 times.

[0044] (9) Mold: The molds used in this experiment are all made of ABS plastic. There are two types of molds used, one is cylindrical, with a size of Φ50mm×100mm; the other is cubic, with a size of 100mm×100mm×100mm. In order to facilitate demolding, lubricating oil needs to be evenly applied inside the mold before filling.

[0045] (10) Agate mortar, used for preparing small amounts of powdered samples for X-ray diffraction and infrared spectroscopy analysis, respectively.

[0046] Example 1

[0047] A ceramsite-gypsum solid waste system rock-like material, prepared from desulfurized gypsum, water-absorbing ceramsite, retarder and water;

[0048] The mass ratio of desulfurized gypsum, water-absorbing expanded clay and retarder is 300:10:0.8; the mass ratio of water to desulfurized gypsum is 0.45:1.

[0049] The water-absorbent expanded clay is obtained by soaking expanded clay with a particle size of 1.1 cm in water for 1 hour.

[0050] The retarder is a plant protein retarder, and the particle size of the desulfurized gypsum is 12 μm.

[0051] The method for preparing the above-mentioned ceramsite-gypsum solid waste system rock-like material comprises the following steps:

[0052] S1. Add desulfurized gypsum, retarder and water into a mixer, stir at 100r / min for 5min until the mixture is uniform, then add water-absorbing ceramsite and continue stirring for 5min. Stop stirring after observing that the gypsum slurry is uniformly wrapped on the outer surface of the ceramsite to obtain a mixed slurry.

[0053] S2. Pour the mixed slurry into a cylindrical mold prepared in advance, and vibrate for 5 minutes until there are no bubbles on the surface of the mixed slurry to obtain a sample.

[0054] S3. After curing the sample at 23° C. for 24 hours, dry it at 40° C. for 24 hours until constant weight is obtained to obtain the rock-like material of the ceramsite-gypsum solid waste system.

[0055] Example 2

[0056] A ceramsite-gypsum solid waste system rock-like material, prepared from desulfurized gypsum, water-absorbing ceramsite, retarder and water;

[0057] The mass ratio of desulfurized gypsum, water-absorbing expanded clay and retarder is 200:15:0.6; the mass ratio of water to desulfurized gypsum is 0.43:1.

[0058] The water-absorbent expanded clay is obtained by soaking expanded clay with a particle size of 0.8 cm in water for 1 hour.

[0059] The retarder is a plant protein retarder, and the particle size of the desulfurized gypsum is 10 μm.

[0060] The method for preparing the above-mentioned ceramsite-gypsum solid waste system rock-like material specifically comprises the following steps:

[0061] S1. Add desulfurized gypsum, retarder and water into a mixer and stir at 80r / min for 3min until the mixture is uniform. Then add water-absorbing ceramsite and continue stirring for 3min. After observing that the gypsum slurry is uniformly wrapped on the outer surface of the ceramsite, stop stirring to obtain a mixed slurry.

[0062] S2. Pour the mixed slurry into a cylindrical mold prepared in advance, and vibrate for 5 minutes until there are no bubbles on the surface of the mixed slurry to obtain a sample.

[0063] S3. After curing the sample at 23°C for 24 hours, dry it at 30°C for 12 hours to constant weight to obtain the rock-like material of the ceramsite-gypsum solid waste system.

[0064] Example 3

[0065] A ceramsite-gypsum solid waste system rock-like material, prepared from desulfurized gypsum, water-absorbing ceramsite, retarder and water;

[0066] The mass ratio of desulfurized gypsum, water-absorbing expanded clay and retarder is 300:25:0.7; the mass ratio of water to desulfurized gypsum is 0.46:1.

[0067] The water-absorbent expanded clay is obtained by soaking expanded clay with a particle size of 1.0 cm in water for 2 hours.

[0068] The retarder is a plant protein retarder, and the particle size of the desulfurized gypsum is 25 μm.

[0069] The method for preparing the above-mentioned ceramsite-gypsum solid waste system rock-like material specifically comprises the following steps:

[0070] S1. Add desulfurized gypsum, retarder and water into a mixer and stir at 100r / min for 4 minutes until the mixture is uniform. Then add water-absorbing ceramsite and continue stirring for 4 minutes. After observing that the gypsum slurry is uniformly wrapped on the outer surface of the ceramsite, stop stirring to obtain a mixed slurry.

[0071] S2. The prepared mixed slurry is introduced into a cylindrical mold prepared in advance, and vibrated for 8 minutes until there are no bubbles on the surface of the mixed slurry to obtain a sample.

[0072] S3. After curing the sample at 27° C. for 36 hours, dry it at 35° C. for 20 hours to constant weight to obtain the rock-like material of the ceramsite-gypsum solid waste system.

[0073] Example 4

[0074] A ceramsite-gypsum solid waste system rock-like material, prepared from desulfurized gypsum, water-absorbing ceramsite, retarder and water;

[0075] The mass ratio of desulfurized gypsum, water-absorbing expanded clay and retarder is 400:35:0.8; the mass ratio of water to desulfurized gypsum is 0.44:1.

[0076] The water-absorbent expanded clay is obtained by soaking expanded clay with a particle size of 1.4 cm in water for 2 hours.

[0077] The retarder is a plant protein retarder, and the particle size of the desulfurized gypsum is 25 μm.

[0078] The method for preparing the above-mentioned ceramsite-gypsum solid waste system rock-like material specifically comprises the following steps:

[0079] S1. Add desulfurized gypsum, retarder and water into a mixer and stir at 120r / min for 5 minutes until the mixture is uniform. Then add water-absorbing ceramsite and continue stirring for 5 minutes. Stop stirring after observing that the gypsum slurry is uniformly wrapped on the outer surface of the ceramsite to obtain a mixed slurry.

[0080] S2. Pour the mixed slurry into a cylindrical mold prepared in advance, and vibrate for 10 minutes until there are no bubbles on the surface of the mixed slurry to obtain a sample.

[0081] S3. After curing the sample at room temperature for 48 hours, dry it at 40° C. for 40 hours to constant weight to obtain the rock-like material of the ceramsite-gypsum solid waste system.

[0082] Example 5

[0083] A ceramsite-gypsum solid waste system rock-like material, prepared from desulfurized gypsum, water-absorbing ceramsite, retarder and water;

[0084] The mass ratio of desulfurized gypsum, water-absorbing expanded clay and retarder is 400:50:0.9; the mass ratio of water to desulfurized gypsum is 0.44:1.

[0085] The water-absorbent expanded clay is obtained by soaking expanded clay with a particle size of 1.4 cm in water for 2 hours.

[0086] The retarder is a plant protein retarder, and the particle size of the desulfurized gypsum is 25 μm.

[0087] The method for preparing the above-mentioned ceramsite-gypsum solid waste system rock-like material specifically comprises the following steps:

[0088] S1. Add desulfurized gypsum, retarder and water into a mixer and stir at 150r / min for 5 minutes until the mixture is uniformly mixed, then add water-absorbing ceramsite and continue stirring for 5 minutes. Stirring is stopped after the desulfurized gypsum slurry is observed to be uniformly wrapped on the outer surface of the ceramsite to obtain a mixed slurry.

[0089] S2. Pour the mixed slurry into a cylindrical mold prepared in advance, and vibrate for 10 minutes until there are no bubbles on the surface to obtain a sample.

[0090] S3. After curing the sample at 25°C for 48 hours, bake it at 40°C for 40 hours to constant weight to obtain the rock-like material of the ceramsite-gypsum solid waste system.

[0091] The uniaxial compressive strength of the rock-like materials of the ceramsite-desulfurized gypsum solid waste system prepared in Examples 1 to 5 is between 2.42 MPa and 2.70 MPa.

[0092] In order to further illustrate the effect of rock-like materials in the ceramsite-desulfurized gypsum solid waste system, the following experiment was conducted. In the following experiment, the mass ratio of water to desulfurized gypsum is uniformly referred to as the water-to-gypsum ratio.

[0093] 1. Effect of ceramsite addition on the properties of rock-like materials in ceramsite-desulfurized gypsum solid waste system

[0094] When the water-paste ratio is fixed at 0.45:1, the content of ceramsite is adjusted to determine the effect of aggregate content on its performance, and the experimental formula is designed as shown in Table 1. Since the maximum ceramsite content that the selected molding mold can accommodate is limited, the ceramsite mass is 90% of the maximum capacity of the mold, that is, 50g, which is considered to be 90% of the ceramsite content in the similar material system of this experiment. By analogy, 6 groups of different ceramsite content formulas are designed, numbered T1, T2, T3, T4, T5, and T6 for experimental research.

[0095] Table 1 Actual sample formula

[0096] serial number Desulfurized gypsum / g Ceramic aggregate / g Water / g Retarder / g Ceramic content / % T1 300 50 135 0.75 90 T2 300 38.9 135 0.75 70 T3 300 27.7 135 0.75 50 T4 300 16.7 135 0.75 30 T5 300 5.6 135 0.75 10 T6 300 0 135 0.75 0

[0097] 2. Effect of water-cement ratio on rock-like materials in ceramsite-gypsum solid waste system

[0098] The water-cement ratio of the rock-like material of the ceramsite-gypsum solid waste system is limited by experiments. When the cement ratio of desulfurized gypsum to ceramsite and the amount of retarder are fixed, the ratio of water to desulfurized gypsum, i.e., the water-cement ratio, is determined, and the setting time is controlled within 24 hours or even less. The optimal water-cement ratio of the rock-like material of the ceramsite-gypsum solid waste system is determined by the fluidity of the slurry and the setting time. The specific sample ratio is shown in Table 2. The mass of the ceramsite is fixed to 90% of the maximum capacity of the mold, i.e., 50g. Five groups of different water-cement ratios are designed, numbered S1, S2, S3, S4, and S5. The mass ratio of desulfurized gypsum to ceramsite is 4:1, and the amount of retarder added is 1g.

[0099] Table 2 Sample formulation

[0100]

[0101]

[0102] Mechanical properties test: demould the completely dried specimens, smoothen both ends with sandpaper, measure the final height and conduct a uniaxial compression test.

[0103] 3. Test methods

[0104] 1) Uniaxial compression test

[0105] The uniaxial compression test is a common rock mechanics test method used to determine the compressive strength and deformation properties of rock when subjected to pressure perpendicular to its surface. The uniaxial compression test is one of the important methods for evaluating the compressive strength and deformation properties of rock, and is widely used in geological engineering, geotechnical engineering, mining engineering and other fields.

[0106] According to GB / T 23561.8-2024, the calculation formulas for stress, strain and elastic modulus are:

[0107]

[0108] Where: σ is stress, MPa; p is the load corresponding to the strain, kN; F is the initial bearing area of ​​the specimen, cm 2 .

[0109]

[0110] Where: ε is strain; ΔL is the deformation of the specimen, mm; L is the original length of the specimen, mm.

[0111]

[0112] Where: E t is the elastic modulus, MPa; σ a is the stress at the beginning of the straight line segment in the stress-strain curve, MPa; σb is the stress at the end point of the straight line segment in the stress-strain curve, MPa; ε a is the strain value at the starting point of the straight line segment in the stress-strain curve; ε b is the strain value at the end point of the straight line segment in the stress-strain curve.

[0113] 2) X-ray diffraction analysis

[0114] X-ray diffraction analysis is a technique used to determine the microstructural parameters of crystalline and certain amorphous materials. The method is based on the principle that different substances have their own unique crystal structures. When a material is irradiated with X-rays of a certain intensity, the crystal planes will reflect secondary fluorescent X-rays according to Bragg's law. Qualitative and quantitative analysis can be performed by analyzing the diffraction angle and the integrated intensity of the spectrum. This analysis method is one of the most commonly used characterization test techniques in scientific research, and data processing usually requires the use of professional software such as Jade and HighScore.

[0115] 3) Scanning electron microscope, abbreviated as SEM

[0116] Scanning electron microscopy uses an electron beam as a light source, scans the surface of a solid sample with a very finely focused electron beam in a raster scanning manner, and obtains surface morphology information of the sample by detecting secondary electrons. The advantages of scanning electron microscopy include multi-angle observation of samples, direct analysis of surface structure, good three-dimensional images, and micro-area analysis. This experiment aims to use scanning electron microscopy to analyze the morphology of each phase, the connection relationship of the interface, etc.

[0117] 4. Parameter evaluation indicators

[0118] 1) Brittleness index

[0119] The rock brittleness index is an evaluation index that describes the brittleness of rocks. It is usually determined by experiments or observations of the failure mode and crack extension of rocks under stress. The higher the value of the brittleness index, the easier it is for the rock to fail in a brittle manner, that is, it is more likely to crack and break after being subjected to a certain stress. In the fields of engineering and geology, understanding the brittleness index of rocks is very important for design and construction. For projects that require drilling, excavation or blasting in rocks. In addition, in geological exploration and mineral exploration, the brittleness index is also one of the important indicators for evaluating rock quality and stability. The brittleness index is an important factor in evaluating the fracturability of shale and predicting collapse, rock bursts and earthquakes. At the same time, brittleness not only has a significant impact on the machinability, drillability and excavability of rocks, but is also closely related to the sustainable mining and safe construction of coal mines. Understanding the brittleness index of rocks can help engineers choose appropriate processes and equipment to reduce the occurrence of accidents.

[0120] This embodiment is to quantitatively evaluate the brittleness of the material. The brittleness index is defined by the total stress parameter of the rock-like material of the ceramsite-gypsum solid waste system. The calculation formula is as follows:

[0121]

[0122] In the formula: BI zhou is the brittleness index, k ac is the slope of the straight line connecting the peak and the residual point; σ p is the peak stress; σ r is the residual strength. zhou When ≤1.0, there is a strong tendency of rock burst; zhou When >1.0, there is no rock burst tendency.

[0123] 2) Impact energy index

[0124] The impact tendency of rock formation refers to its property of accumulating deformation energy and producing impact damage. It is used to judge the rockburst tendency of rock. The energy impact index A proposed by Gong Fengqiang et al. is introduced. CF , the index is defined by the rock total stress-strain curve and is calculated as follows:

[0125]

[0126] Where: A CF is the impact energy index. A1 is the area before the peak, and A2 is the area after the peak. CF >3.0, similar materials have strong rock burst; 2.0 <A CF When ≤3.0, similar materials have medium rock burst; 1.0≤A CF When ≤2.0, similar materials have weak rock burst; A CF When <1.0, similar materials have no rock burst.

[0127] 3) Determination of water-paste ratio

[0128] The setting time and fluidity of samples S1, S2, S3, S4 and S5 were measured respectively, and the results are shown in Table 3.

[0129] Table 3 Experimental data table

[0130]

[0131] As shown in Table 3, it can be seen from the fluidity data that the amount of water added has a great influence on it. As the water-paste ratio decreases, the fluidity of the slurry decreases significantly. S1 is too thin and it is not easy to hang on the blades during stirring. S5 is too thick and the machine stops. Manual mixing is required, and the sample does not collapse when the fluidity is measured. During grouting, the desulfurized gypsum slurry is too thick to be fully mixed with the expanded clay. If it is too thin, the expanded clay will float when vibrated, which also affects the uniformity of the specimen and further affects its strength. The water-paste ratios of S2, S3, and S4 can be well mixed with the expanded clay and are easier to mix. Therefore, the water-paste ratio suitable for the solidification of similar materials is determined to be 0.43-0.47.

[0132] The water-paste ratio determines the curing time of desulfurized gypsum and the mechanical properties of the sample. If the water-paste ratio is too high, the water is not easy to remove, the curing time is too long, the fluidity of the slurry is too large, and the ceramsite is easy to float on the surface of the slurry due to its porous structure, affecting the dispersion of the ceramsite in the slurry. If the water-paste ratio is too low, the curing rate of the slurry is accelerated, the fluidity is low, the slurry is difficult to stir evenly, the internal bubbles are not easy to discharge, and the uniformity of the structure of similar materials is also seriously affected. The uniform dispersion of aggregates in the slurry, the water content inside the system, and the pore content will all affect the mechanical properties of similar materials, and the resulting changes in mechanical properties are random fluctuations and irregular. Therefore, the present invention experiments on the water-paste ratio of ceramsite-desulfurized gypsum similar material system to determine the water-paste ratio suitable for the curing and molding of the similar material.

[0133] 4) Effect of aggregate content on performance

[0134] The uniaxial compression test of cylindrical specimens was carried out on the specimens with different ceramsite contents, and the stress-strain curves were obtained, such as Figure 1 The data are shown in Table 4.

[0135] Table 4 Experimental data table

[0136]

[0137] The impact energy index increases with the increase of aggregate content. T2 and T4 have strong rock burst; T1 has moderate rock burst; T3 and T6 have weak rock burst; T5 has no rock burst, which is quite abnormal. The brittleness index is less than 1, and the specimen has a tendency to rock burst. Analysis of stress-strain curve Figure 1 It can be seen that the curve drops rapidly after reaching the peak strength, showing brittle failure characteristics, and can be preliminarily judged as a brittle material. The brittle failure characteristics of the two groups T2 and T4 are more obvious, and the curve drops sharply when loaded to the peak strength. From the data, as the amount of ceramsite added increases, its peak strength tends to decrease step by step, and the optimal ceramsite content suitable for the molding of similar materials is determined to be 30% to 70%.

[0138] The present invention conducts experiments on the influence of ceramsite content on mechanical properties of ceramsite-desulfurized gypsum similar material system, and determines that the optimal ceramsite content suitable for the preparation and molding of the similar material is 30% to 70%. The stress-strain curve of the prepared cubic T2 sample and the sample photo after uniaxial compression strength test are shown in Figure 2. Figure 2 As shown. It can be seen that the uniaxial compressive strength is 1.9MPa, and the stress-strain curve drops rapidly after reaching the peak strength, showing brittle failure characteristics. It can be preliminarily judged as a brittle material, and the strength meets the specified range. In the scanning electron microscope, a large number of prismatic or irregularly shaped crystals can be seen, namely calcium sulfate dihydrate, which is the product of the hydration of hemihydrate gypsum and the crystallization of dihydrate gypsum in water. The microscopic morphology of the cubic T2 sample in Example 2 is shown in FIG. Figure 3 As shown in the figure, the loose and porous microstructure is ceramsite, which can store a certain amount of water when mixed with water and gypsum. In the later stage of the reaction, it continuously supplies water for the hydration reaction, so that the semi-hydrated gypsum is completely hydrated and completely converted into dihydrate gypsum with a hard structure. It can be observed from the cross section that the combination of gypsum and ceramsite is weak, and the contact interface is clear. The porous ceramsite is judged to be located at the junction of the two substances. At the same time, a small number of gypsum pits were observed, indicating that when the specimen was subjected to external stress, the material fractured mainly in the form of fracture of the porous structure of ceramsite, and some fractures occurred along the contact surface, which was mainly caused by the weak combination between the two substances.

[0139] The present invention aims at the rock stratum movement, collapse and rock burst safety accidents that are easy to occur during deep coal mining. By conducting physical model simulation experiments in the laboratory, the present invention makes full use of solid waste resources such as ceramsite and desulfurized gypsum to make rock-like materials. The present invention tests its various parameters under the influence of different factors and conditions through uniaxial compression tests. It can be seen from the various results that as the content of ceramsite aggregate increases, the compressive strength decreases, and the impact energy index increases from 1.24 to 2.53; as the content of ceramsite aggregate increases, the brittleness index ranges from 0.14 to 0.88, and the elastic modulus decreases from 0.88GPa to 0.14GPa. At the T2 ratio, that is, 70% ceramsite content, the water-paste ratio is 0.45, the compressive strength is 2.70MPa, the impact energy index is 7.7, the brittleness index is 0.23, and the elastic modulus is 0.38GPa. It shows high rock burst characteristics and brittle fracture failure forms.

[0140] The optimal water-cement ratio in the present invention is 0.45, the optimal ceramsite content is 70%, and the obtained ceramsite-gypsum solid waste system has a rock-like material strength of no more than 3MPa and exhibits brittle failure characteristics, which meets the requirements for low-strength and high-brittle similar materials. This ratio complies with the national standard GB / T23561.8-2024 for the determination of physical properties of coal and rock.

[0141] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0142] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A rock-like material of ceramsite-gypsum solid waste system, characterized in that: The rock-like material of the ceramsite-gypsum solid waste system is prepared from desulfurized gypsum, water-absorbing ceramsite, a retarder and water; The mass ratio of the desulfurized gypsum, the water-absorbing ceramsite and the retarder is 200-400: 5-50: 0.5-0.9; The mass ratio of the water to the desulfurized gypsum is 0.43-0.47:1; The water-absorbing ceramsite is obtained by soaking the ceramsite in water.

2. The ceramsite-gypsum solid waste system rock-like material according to claim 1, characterized in that: The retarder is a vegetable protein retarder.

3. The ceramsite-gypsum solid waste system rock-like material according to claim 1, characterized in that: The particle size of the ceramsite is 0.8 cm to 1.4 cm, and the particle size of the desulfurized gypsum is 10 μm to 25 μm.

4. The ceramsite-gypsum solid waste system rock-like material according to claim 1, characterized in that: The soaking time is 1 h to 2 h.

5. A method for preparing a rock-like material of a ceramsite-gypsum solid waste system according to any one of claims 1 to 4, characterized in that: The following steps are involved: The desulfurized gypsum, retarder and water are mixed and stirred according to the mass ratio, and the water-absorbing ceramsite is added and stirred continuously to obtain a mixed slurry; the mixed slurry is injected into a mold, and compacted to obtain a sample; The sample is cured at 23° C. to 27° C. for 24 h to 48 h, then demolded and dried to constant weight to obtain the ceramsite-gypsum solid waste system rock-like material.

6. The method for preparing rock-like materials of ceramsite-gypsum solid waste system according to claim 5, characterized in that: The mixing and stirring is performed at a speed of 60 to 150 r / min and a time of 3 to 5 min; Add the water-absorbing expanded clay and continue stirring for 3 to 5 minutes.

7. The method for preparing rock-like materials of ceramsite-gypsum solid waste system according to claim 5, characterized in that: The drying temperature is 30° C. to 40° C., and the drying time is 12 h to 40 h.

8. The method for preparing rock-like materials of ceramsite-gypsum solid waste system according to claim 5, characterized in that: The compaction standard is that there are no bubbles on the surface of the mixed slurry.

9. Use of the ceramsite-gypsum solid waste system rock-like material according to any one of claims 1 to 4 in a rock simulation experiment.

10. The use according to claim 9, characterized in that: The ceramsite-gypsum solid waste system rock-like material is used to simulate low-strength and high-brittle rock simulation materials with a uniaxial compression strength not exceeding 3 MPa.

Citation Information

Patent Citations

  • Hard rock similar model test material and preparation method thereof

    CN105967562A

  • Hard rock-simulating transparent similar model test material and preparation method thereof

    CN109679291A

  • Similar material for extrusion type 3D printing of tunnel lining model

    CN118084433A

  • Sandstone similar material based on freeze-thaw cycle model tests and preparation method thereof

    CN110294617A

  • Manufacturing method of test model for simulating stratified jointed rock mass similar material

    CN110850061A